INTEGRATING ISLAMIC EDUCATION VALUES: THE KEY TO CHARACTER EDUCATION OF THE YOUNG GENERATION AL-HIKAM PERSPECTIVE - Hidayat, Ichwan Kurnia (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study was to determine integrating Islamic education values as the key to character education Al-Hikam perspective to the young generation at SMPN 2 Balongbendo. This study used field survey research using a descriptive qualitative approach. The results of this study that Al-Hikam integrates the values of Islamic education through various methods. The main approach was thematic learning, where the subject matter was designed to reflect Islamic values such as honesty, responsibility, and social care. Extracurricular activities such as recitation, memorization of the Quran, and social activities also strengthen character values. In addition, teachers at Al-Hikam serve as role models in practicing Islamic values in daily life, providing concrete examples for students. The impact of this integration of Islamic values was very positive for students. Based on interviews with 32 students, there were improvements in honesty, discipline, and a sense of responsibility. Observations showed that students become more religious and have a deep understanding of Islamic teachings. Academic data showed a positive correlation between the integration of Islamic values with students' academic achievement, where 80% of students recorded an increase in grades after applying this method.